Inclusive Education and CWSN — Parental Concerns and Expectations - Islam, Quazi Ferdoushi (THE PRIMARY TEACHER, 2017)
There has been an increase in awareness advocacy regarding inclusion in education by various stakeholders, including organisations at the national and international level. Policies and initiatives across the globe have addressed the issue of introducing and implementing measures to facilitate meaningful participation of Children with Special Needs (CWSN) in regular schools. The Central and State governments in India, too, have been implementing programmes and policies for the inclusion of CWSN in regular schools. The Right to Education (RTE) Act, 2009, also guarantees free education to every child in the age group of 6–14 years. But a reality check at seven government and municipal schools in two districts of Delhi (East and North East Delhi) reveals that these children are still amongst the most disadvantaged in terms of access to schooling and completion of education, as their basic needs are not yet being met. This paper highlights some of the concerns and expectations of parents of CWSN, studying at primary government or municipal schools in East and North East Delhi.